El proceso de toma de decisiones basado en métodos cuantitativos: Análisis de tendencias en el ámbito corporativo; Analysis of research on decision making-based on quantitative methods - Emilio Abad-Segura; Mariana Daniela González-Zamar; Eloy López-Meneses (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– Economic activity occurs in a changing and globalized environment. Thus, business decisions that are made in a competitive context and with asymmetric information are based, mainly, on quantitative elements that, based on decision models, allow information to be obtained that facilitate the optimization of these decisions. This study aims to analyse scientific production and research trends on decision-making based on quantitative methods. For this, bibliometric techniques were applied to a sample of 1,143 articles from the 1967-2019 period obtained from the Scopus database. The VOSviewer software tool was used to build and visualize bibliometric networks. The purpose was to recognize the disciplines and the evolution of these areas of interest, in addition to identifying the networks by co-authorship of the main authors, research institutions and countries, and the network of keywords by co-occurrence, through the application of visualization techniques. The interest of this field of research in the research community is verified, with optimal rates of publication and collaboration among its driving agents.
Keywords: G30; F65; O16; 330; decision making; quantitative methods; business; research